(untitled) (Politeja, 2020)
Polexit in the Light of the Results of Public Opinion Polls In 2015, presidential and parliamentary elections took place in Poland and, as a result, the pro‑European parliamentary coalition of Platforma Obywatelska (Civic Platform) and Polskie Stronnictwo Ludowe (Polish People’s Party) lost power after eight years of governing. The winning conservative coalition consisted of three parties: Law and Justice, Solidarity Poland and Jaroslaw Gowin’s Agreement party. From the very beginning, on various occasions (relocation of immigrants, reforms of the judiciary, rule of law) there have been disputes between the new authorities in Warsaw and the EU institutions (European Commission, European Parliament, Court of Justice of the European Union). The concept of polexit appeared in public discourse as one of the possible options for resolving these conflicts. The author of this article undertook the task of analyzing the results of research on the attitude of Polish society to Poland’s membership in the European Union in search of the answer to the question whether in the light of these results polexit is possible and whether it is not possible to repeat the British scenario that led to Brexit.